2006
DOI: 10.1002/jgm.896
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic level of functional human alpha 1 antitrypsin (hAAT) secreted from murine muscle transduced by adeno‐associated virus (rAAV1) vector

Abstract: Alpha 1 antitrypsin (AAT) is a serine proteinase inhibitor (serpin). One well-known function of this protein is to inactivate neutrophil elastase and other neutrophil-derived proteinases, and prevent the destruction of pulmonary extracellular matrix. Deficiency of AAT can cause emphysema due to degradation of interstitial elastin by elastase. The majority of circulating AAT is secreted from the liver. Muscle-directed gene therapy using recombinant adeno-associated virus 2 (rAAV2) vectors has been tested to inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Long-term and high levels of transgene expression have been achieved in animal models as well as in humans (9,17,18). However, the host immune response to a transgene product is one of the major hurdles to limit the successes of gene therapy in humans (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Long-term and high levels of transgene expression have been achieved in animal models as well as in humans (9,17,18). However, the host immune response to a transgene product is one of the major hurdles to limit the successes of gene therapy in humans (19).…”
Section: Discussionmentioning
confidence: 99%
“…rAAV vectors were purified using iodixanol (IOD) gradients. The physical particle titers were determined by a dot-blot assay (9).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has a very limited packaging capacity, however (approximately 5 kb), and the original AAV2 is relatively inefficient at infecting a number of key cell types. Studies are now underway in the US and Europe with rAAV1 vectors, which have been shown to be nearly 1,000-fold more potent for murine muscle transduction than rAAV2 vector (Chao et al, 2000;Lu et al, 2006). Over 100 capsid variants are now known to exist (Gao et al, 2002.…”
Section: Attempts To Improve Vector Designmentioning
confidence: 99%